The effects of phase-modulated excitation on the focused acoustic field - Zhou, Yufeng (2022)
Various modulation approaches, such as amplitude and frequency modulations, have been applied widely to modify the acoustic field and improve the performance of ultrasound imaging and therapy. However, phase modulation (PM) has not been investigated extensively in the ultrasound applications, especially at a long-pulse duration. In this study, the effects of PM on the acoustic field were investigated. The radiated acoustic pressure waveforms produced using different PM strategies (i.e., sequential phase inversion every cycle, every two cycles, and random phase inversion) were explored, and the distributions of acoustic pressure and average acoustic intensity along and transverse to the transducer axis were compared with those of a sinusoidal wave excitation in both measurement and simulation. It is found that the phase inversion between the modulated signals is not clearly seen in the radiated waveform because of the limited fractional bandwidth of the therapeutic ultrasound transducer. As a result, the radiated waveform has a higher oscillating frequency, and the pressure at the focus and the -6-dB beam size are decreased. Both simulation and measurement show similar trends. Furthermore, produced acoustic fields of the phased array using these PM strategies were also simulated at the varied lateral and axial focus shifting distances. The magnitude and beam size of both the main lobe and grating lobe are found between them, especially at the large focus shifting. In summary, the acoustic field is dependent on the PM, and the appropriate excitation scheme could improve the ultrasound application.